(untitled) (Economic studies journal, 2019)
" This research studied the effect of the factors of production on the agricultural economy. One of the objectives was to analyze and measure the effect of the factors of production on the agricultural economy and the importance of agricultural output on the local production and to get knowledge of the nature of the function of the Libyan agricultural production and the nature of the relationship between agricultural employment and fixed capital formation (FCF). This research study was carried out based on a model to prove the hypothesis (Direct investment and agricultural employment) on the volume of agricultural output in Libya during the period of (1992-2012). The resuHGlts of the descriptive and standard analysis showed that the independent variables (fixed capital formation and agricultural employment) have positive impact on the agricultural gross local product in the short and long-term of time, and that the estimated statistically significant statistical model, and this model-free assessment problems”.